Synthesis of NaP Zeolite Based on Bauxite Red Mud Using Hydrothermal Method on Mole Ratio of SiO2/Al2O3 Variations - Eviva, Nur; Shofiyani, Anis; Sayekti, Endah (POSITRON, 2023)
Red mud is a bauxite industrial waste of reddish-brown mud with high alkalinity. Red mud has relatively high silica and alumina content, so it can be utilized as a raw material in the synthesis of zeolite. This study aims to synthesize high-purity NaP zeolite from red mud at various SiO2/Al2O3 mole ratios. The synthesis begins with neutralizing the red mud, followed by decomposition using the alkaline fusion method at a ratio of red mud:NaOH = 1:1 (w/w). The filtrate produced by the alkaline fusion was adjusted to the mole ratio of SiO2/Al2O3 = 2.0; 2.5; 3.0; and 4.0, respectively, by adding sodium silicate, followed by a hydrothermal process using an autoclave at 120oC for 16 hours. The synthesized zeolites were characterized using XRD and FTIR spectrophotometry. The XRD results showed that the zeolite produced in all variations of the SiO2/Al2O3 mole ratio studied was a type of high-purity NaP with no other zeolite crystalline phases found as impurities. The structure formed is tetragonal with a degree of crystallinity of 74.54%; 76.47%; 78.94%; 75.64%, and crystal size 80.2286; 54.3437; 37.7099 and 40.1226 nm for zeolite with SiO2/Al2O3 mole ratio 2.0; 2.5; 3.0; and 4.0, respectively. Based on the results of the study, pure NaP zeolite can be synthesized from red mud material using the hydrothermal method at the ratio of moles SiO2/Al2O3 = 2.0 – 4.0.